Sesamin alleviates lipid accumulation induced by elaidic acid in L02 cells through TFEB regulated autophagy - Liang, Xueli; Zhang, Tianliang; Cheng, Xinyi; Yuan, Hang; Yang, Ning; Yi, Yanlei; Li, Xiaozhou; Zhang, Fengxiang; Sun, Jinyue; Li, Zhenfeng; Wang, Xia (Frontiers in Nutrition, 2024)
IntroductionNon-alcoholic fatty liver disease (NAFLD) is a common chronic disease seriously threatening human health, with limited treatment means, however. Sesamin, a common lignan in sesame seed oil, exhibits anti-inflammatory, antioxidant, and anticancer properties. Our previous studies have shown an ameliorative effect of sesamin on lipid accumulation in human hepatocellular carcinoma (HePG2) induced by oleic acid, with its protective effects unclear in the case of 9-trans-C18:1 elaidic acid (9-trans-C18,1).MethodsL02 cells, an important tool in scientific researches due to its high proliferation ability, preserved hepatocyte function, and specificity in response to exogenous factors, were incubated with 9-trans-C18:1 to establish an in vitro model of NAFLD in our study. The lipid accumulation in cells and the morphology of mitochondria and autolysosomes were observed by Oil Red O staining and transmission electron microscopy. The effects of sesamin on oxidative stress, apoptosis, mitochondrial function, autophagy as well as related protein levels in L02 cells were also investigated in the presence of 9-trans-C18:1.ResultsThe results showed that sesamin significantly accelerated the autophagy flux of L02 cells induced by 9-trans-C18:1 as well as elevated protein levels of transcription factor EB (TFEB) and its downstream target lysosome-associated membrane protein 1(LAMP1), along with up-regulated levels of TFEB and LAMP1 in the nucleus indicated by Immunofluorescence. In addition, PTEN-induced putative kinase 1 and Parkin mediated mitophagy was activated by sesamin. The direct inhibitor Eltrombopag and indirect inhibitor MHY1485 of TFEB reversed the protective effect of sesamin, suggesting the involvement of autophagy in the lipid-lowering process of sesamin.DiscussionThis work suggests that sesamin regulates autophagy through TFEB to alleviate lipid accumulation in L02 cells induced by 9-trans-C18:1, providing a potential target for the prevention and treatment of NAFLD.